Genetic and Phenotypic Variation in Tree Crops Biodiversity - Distefano, Gaetano (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Recently, there has been a dramatic increase in the use of DNA-derived data and innovative phenotyping to obtain insights into the causative genes underlying traits of agronomical interest or to characterize tree genetic resources. The latter, in particular, could represent an important source of genetic diversity that can be readily used to enhance the adaptability to limiting environmental factors and resistance to biotic stresses or to promote novel genotypes with improved agronomic traits. On the whole, the studies collected in this book report on tree crop biodiversity characterization that could provide the essential building blocks to ensure future improvements in production and quality, as well as for innovations in tree crop development and utilization.